2016
DOI: 10.1086/683832
|View full text |Cite
|
Sign up to set email alerts
|

Credible Sources and Sophisticated Voters: When Does New Information Induce Economic Voting?

Abstract: When does new economic information cause voters to re-evaluate the government's competence, and ultimately vote economically? Since politically-relevant information is often conveyed by actors with incentives to influence voter perceptions, the credibility of information sources can vary significantly. This article randomly varies whether voters receive an aggregate unemployment forecast from the central bank, government or main opposition party using a survey experiment in Denmark with access to detailed pane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 54 publications
2
38
1
Order By: Relevance
“…5 This attention to voters' information environments follows recent work in political economy (e.g. Alt, Lassen, and Marshall 2016;Iversen and Soskice 2015; We study the UK case, and provide evidence of three important relationships. First, in observational data, attitudes towards the deficit vary systematically with the newspapers that people read, even when partisan identification and a range of other covariates are accounted for.…”
Section: Introductionmentioning
confidence: 83%
“…5 This attention to voters' information environments follows recent work in political economy (e.g. Alt, Lassen, and Marshall 2016;Iversen and Soskice 2015; We study the UK case, and provide evidence of three important relationships. First, in observational data, attitudes towards the deficit vary systematically with the newspapers that people read, even when partisan identification and a range of other covariates are accounted for.…”
Section: Introductionmentioning
confidence: 83%
“…Unlike sophisticated voters [12], unsophisticated voters do not take the rational behaviour of the rest of society into account. Unsophisticated voters take decisions on the basis of a distorted perception of reality or do not link their perception to their voting decision, whereas sophisticated voters are empirically found to (typically) form correct expectations and vote rationally according to Alt, Lassen and Marshall [13]. Aidt (p. 359) [14], concludes that “voters may not be fully informed but they know enough to make rational and informed decisions”, whereas Aidt and Dutta (p. 354) [15] contend that “other groups (the poor and uneducated) … are … unlikely to cast rational … votes”.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies so far explore this link within consolidated democracies such as the ones found with the degree and the direction of the endorser's bias. Alt et al (2016) find that economic information acquired from the Danish Central Bank causes voters to better update their belief when compared to information received from the government or political parties.…”
Section: Introductionmentioning
confidence: 90%